2007
DOI: 10.1001/archfaci.9.5.314
|View full text |Cite
|
Sign up to set email alerts
|

Transglabellar Subcranial Approach for the Management of Nasal Masses With Intracranial Extension in Pediatric Patients

Abstract: The subcranial approach is an effective technique for the resection of nasal masses with intracranial extension. These lesions have traditionally been managed with lateral rhinotomy, midface degloving, or external rhinoplasty approaches combined with a frontal craniotomy. The subcranial approach offers several advantages over a traditional frontal craniotomy. It provides excellent exposure, minimizes frontal lobe retraction, reduces the likelihood of cerebrospinal fluid leakage, and provides for an excellent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This can be performed through an endonasal, endoscopic approach or via a craniotomy. 19,20 Surgical approaches to anterior skull base encephaloceles have evolved in the recent decades. Endoscopic endonasal surgery has become more widely adopted as a viable approach.…”
Section: Meningoencephalocelementioning
confidence: 99%
“…This can be performed through an endonasal, endoscopic approach or via a craniotomy. 19,20 Surgical approaches to anterior skull base encephaloceles have evolved in the recent decades. Endoscopic endonasal surgery has become more widely adopted as a viable approach.…”
Section: Meningoencephalocelementioning
confidence: 99%
“…[252627] Other disadvantages include more chances of brain parenchymal injuries as it involves frontal lobe retraction, large external scar, and more chances of cerebrospinal fluid (CSF) leak. [27]…”
Section: Discussionmentioning
confidence: 99%
“…[25] The greatest disadvantage of this approach is that it requires to be combined with other transfacial or endoscopic approaches for successful resection of large tumor mass with nose and paranasal sinus involvement. [25][26][27] Other disadvantages include more chances of brain parenchymal injuries as it involves frontal lobe retraction, large external scar, and more chances of cerebrospinal fluid (CSF) leak. [27] The subcranial approach is an effective technique for the resection of nasal masses with intracranial extension.…”
Section: Discussionmentioning
confidence: 99%
“…Kellman et al 6 in 2004 published their results of this approach in three patients with uncomplicated nasal dermoid cysts. In 2007, this group published another communication 7 and concluded that the technique is effective in younger patients, provides excellent exposure, minimizes frontal lobe retraction and cerebrospinal fluid fistulas, and has excellent cosmetic results. Follow-up of these patients showed that their facial growth was not impaired.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In the medical literature, there are few publications on this approach in pediatric patients. [6][7][8] From January 1996 to October 2008 in the Plastic and Reconstructive Surgery Unit at a Children Hospital of Buenos Aires, we used the subcranial approach in a limited number of pediatric patients with nontraumatic pathology. The purpose of this article is to communicate this experience.…”
mentioning
confidence: 99%